Complications during retrograde approach for chronic coronary total occlusion: Sub‐analysis of Japanese multicenter registry. Issue 1 (30th November 2015) - Okamura, Atsunori; Yamane, Masahisa; Muto, Makoto; Matsubara, Tetsuo; Igarashi, Yasumi; Nakamura, Shigeru; Muramatsu, Toshiya; Fujita, Tsutomu; Oida, Akitsugu; Tsuchikane, Etsuo
Abstract : Objectives: This study was performed to determine the complications occurring during retrograde percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) based on analysis of the multicenter, prospective, nonrandomized Retrograde Summit registry. Background: Retrograde PCI for CTO has improved treatment success rates, but several complications related to the retrograde approach have been reported, including collateral channel injury and donor artery injury due to their use as retrograde roots. Methods: This registry included data from 1, 166 patients who underwent retrograde PCI for CTO in 28 Japanese centers between January 2009 and December 2011. Results: Overall procedure success and retrograde procedure success were achieved in 985 (84.5%) and 838 (71.9%) of the 1, 166 patients, respectively. In‐hospital major adverse cardiac and cerebrovascular events (MACCE) occurred in 18 (1.5%) of the 1, 166 patients. With regard to complications related to the retrograde approach, channel injury occurred in 111 (9.5%) of the 1, 166 patients, but treatment was required in only 24 (2.1%) patients and subsequent cardiac tamponade occurred in only 4 (0.3%) patients. Donor artery problems occurred in only 10 (0.9%) of the 1, 166 patients. In sub‐analysis regarding the types of collateral channels, the septal channel was significantly safer than epicardial channel because of the lower frequency of non‐Q‐wave myocardial infarction (non‐QMI) and channel injury requiring treatment. Conclusions: The MACCE rate during retrograde PCI for CTO determined from the Retrograde Summit registry was low and the frequency of complications related to the retrograde approach was acceptable. © 2015 Wiley Periodicals, Inc.